Migrant health in French Guiana: Are undocumented immigrants more vulnerable? - Jolivet Anne; Cadot Emmanuelle; Florence Sophie; Lesieur Sophie; Lebas Jacques; Chauvin Pierre (BMC, 2012)
Abstract Background Few data exist on the health status of the immigrant population in French Guiana. The main objective of this article was to identify differences in its health status in relation to that of the native-born population. Methods A representative, population-based, cross-sectional survey was conducted in 2009 among 1027 adults living in Cayenne and St-Laurent du Maroni. Health status was assessed in terms of self-perceived health, chronic diseases and functional limitations. The migration variables were immigration status, the duration of residence in French Guiana and the country of birth. Logistic regression models were conducted. Results Immigrants account for 40.5% and 57.8% of the adult population of Cayenne and St-Laurent du Maroni, respectively. Most of them (60.7% and 77.5%, respectively) had been living in French Guiana for more than 10 years. A large proportion were still undocumented or had a precarious legal status. The undocumented immigrants reported the worst health status (OR = 3.18 [1.21-7.84] for self-perceived health, OR = 2.79 [1.22-6.34] for a chronic disease, and OR = 2.17 [1.00-4.70] for a functional limitation). These differences are partially explained by socioeconomic status and psychosocial factors. The country of birth and the duration of residence also had an impact on health indicators. Conclusion Data on immigrant health are scarce in France, and more generally, immigrant health problems have been largely ignored in public health policies. Immigrant health status is of crucial interest to health policy planners, and it is especially relevant in French Guiana, considering the size of the foreign-born population in that region.